2020
DOI: 10.1177/0093854820924834
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Neighborhood Typology and Sociodemographic Characteristics on Time to Recidivism Among Adjudicated Youth

Abstract: This study examined the effect of neighborhood disadvantage and criminogenic risk on juvenile recidivism. The sample included 893 youths involved in the delinquency/formal probation division of one Midwestern county juvenile court between 2004 and 2010. Juveniles were classified into one of three neighborhood typologies (i.e., Distressed/Disadvantage, Resilient/Mixed, Benchmark/Advantaged) based on the socioeconomic conditions in their neighborhoods. Survival models revealed that when examining the effect of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…This indicates that despite their overall low risk, many youths come into contact with the juvenile justice system on a relatively consistent basis. One potential explanation is unmeasured ecological factors that may influence the likelihood of contact with the system (Campbell et al, 2020; Onifade et al, 2011). For example, youth within this domain may often come from disadvantaged neighborhoods, which may increase the chance that individuals come into contact with the justice system.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that despite their overall low risk, many youths come into contact with the juvenile justice system on a relatively consistent basis. One potential explanation is unmeasured ecological factors that may influence the likelihood of contact with the system (Campbell et al, 2020; Onifade et al, 2011). For example, youth within this domain may often come from disadvantaged neighborhoods, which may increase the chance that individuals come into contact with the justice system.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that certain macro-level factors influence recidivism (Kirk, 2009; Kubrin & Stewart, 2006). Others have found contrary evidence thus warranting further investigation of the topic (Campbell, 2012; Stahler et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Although decisions have traditionally been made via the professional judgment of practitioners, actuarial risk assessment tools have been adopted to aid in this process (Dawes et al, 1989). Many empirical studies have shown that these instruments improve the accuracy and consistency of correctional evaluations such as individuals’ progress in treatment and their risk of recidivism (Bonta, 2002; Bonta & Andrews, 2007; Campbell, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations